Mission design and analysis of USM high-altitude balloon / Ahmad Shaqeer Mohamed Thaheer and Norilmi Amilia Ismail - Mohamed Thaheer, Ahmad Shaqeer; Ismail, Norilmi Amilia (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
High-altitude balloons (HABs) are unmanned balloons, which are usually filled with helium or hydrogen and can float over approximately 50 km above the sea level. This study aims to develop the mission planner and hardware associated with HAB. The main system of HAB is divided into five subsystems, namely, balloon and navigation, communication, on-board data handling and payload, structure, and thermal system. The design process starts by determining the mission requirements. Through the mission timeline, the flight time is estimated to configure the mode of operation for the mission. A tradeoff analysis is conducted on selected components. The initial selected components that are suitable for the mission are tested individually based on several case studies. After the component testing, the subsystems are integrated and are tested as a whole system. Based on the preliminary results, the configuration and design of the HAB is finalized and a test launch is performed. Finally, the flight test results are collected and analyzed.